Exploring the Essence of Islamic Education in the Modern Era: Ibn Kathir's Perspective on Surah Al-'Alaq Verses 1-5 - Muhammad Fajrin Haikal; Cucu Surahman; Elan Sumarna (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2025)
Education is a key element in the development of both individuals and society, in both general and specific contexts. Broadly speaking, education encompasses a lifelong learning process that has a positive impact, while in a narrower sense, it refers to formal educational institutions. The right to education is guaranteed by the Indonesian Law No. 20 of 2003 and is emphasized in the Qur’an, especially in Surah Al-‘Alaq. This study aims to explore the essence of Islamic education in the modern era, based on verses 1-5 of Surah Al-‘Alaq, through the interpretation of Ibn Kathir. A qualitative approach is used in this study, employing library research as the research method. Based on the analysis of Ibn Kathir’s tafsir on Surah Al-‘Alaq, it is found that education and learning are forms of mercy from Allah SWT, teaching humanity things they did not know before. Islamic education plays an important role in shaping the character and morals of individuals according to religious teachings, while integrating general knowledge with religious principles. Ibn Kathir’s tafsir in this Surah highlights the importance of reading, writing, and learning tawhid. Reading in the name of Allah SWT is considered to bring blessings and knowledge, while writing is necessary for preserving and safeguarding knowledge. Tawhid, which is the core of Islamic teachings, plays a crucial role in building awareness and devotion to Allah SWT. The paradigms of Islamic education based on the tafsir of Surah Al-‘Alaq include (1) the holistic education paradigm, (2) the tawhid-based education paradigm, and (3) the sustainable education paradigm. Overall, Islamic education aims to cultivate individuals who are not only intellectually intelligent but also possess high moral and spiritual values.